1994
DOI: 10.1002/art.1780370711
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characterization of inflammatory cells and immunologic activation markers in muscle and nerve biopsy specimens from patients with systemic polyarteritis nodosa

Abstract: Objective. To investigate the phenotype of infiltrating cells in classic lesions of polyarteritis nodosa (PAN).Methods. Twenty-one muscle and 10 sural nerve biopsy samples from 24 patients with systemic PAN were studied using avidin-biotin-peroxidase and alkaline phosphataseanti-alkaline phosphatase immunohistochemical techniques.Results. The inflammatory infiltrates consisted mainly of macrophages (41%) and T lymphocytes (41 %), particularly of the CD4+ subset. Granulocytes were present in varying quantities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 30 publications
3
27
0
2
Order By: Relevance
“…The vascular pathology in chronically T. cruzi-infected mice has some features that resemble human polyarteritis nodosa (PAN) with regard to multiorgan involvement of medium-sized to small arteries (21), fibrinoid necrosis, mixed cellular infiltrates including pathogen-specific CD8 ϩ T cells and macrophages (22), lack of immune complex deposition in lesions, and involvement of muscles, skin, and nerves (23)(24)(25)(26). The most notable and interesting differences between the mouse vasculitis we analyzed and PAN include an absence in the mouse of the eponymous skin vasculitic nodules found in human PAN, a lack of neutrophilic inflammation in the mouse, and the relative prominence of the extreme involvement of skeletal muscle in the mouse, which is associated with muscle weakness and paralysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vascular pathology in chronically T. cruzi-infected mice has some features that resemble human polyarteritis nodosa (PAN) with regard to multiorgan involvement of medium-sized to small arteries (21), fibrinoid necrosis, mixed cellular infiltrates including pathogen-specific CD8 ϩ T cells and macrophages (22), lack of immune complex deposition in lesions, and involvement of muscles, skin, and nerves (23)(24)(25)(26). The most notable and interesting differences between the mouse vasculitis we analyzed and PAN include an absence in the mouse of the eponymous skin vasculitic nodules found in human PAN, a lack of neutrophilic inflammation in the mouse, and the relative prominence of the extreme involvement of skeletal muscle in the mouse, which is associated with muscle weakness and paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…It will also be interesting and important in future work to define (i) whether a persistent low level of parasites is required to maintain vasculitis lesions in the model, (ii) how innate and adaptive immune responses in the lesions are coordinated and regulated, (iii) why the immune response is localized mainly to arteries and arterioles, and (iv) the mechanism of fibrinoid necrosis. In PAN, the latter is thought to be the result of neutrophil degranulation, but specific molecular details are lacking (22). It is interesting to speculate that localization of the inflammation to arterioles may be the result of an incomplete chemoattractant relay from blood to tissue that is, on the one hand, sufficiently large to stage immune cells at vessels in infected tissue but, on the other hand, insufficient to trigger robust migration to infected microdomains.…”
Section: Discussionmentioning
confidence: 99%
“…25 We have proposed that angiogenesis may play a dual role in vasculitis which, in this regard, is unique among chronic inflammatory disorders. [13][14][15][16][17][18] Neovessels are the main site where endothelial cell adhesion molecules for leukocytes are expressed in medium-sized and large vessel vasculitis such as HUVECs differentiate into capillary-like structures on Matrigel. At low (2%) human serum concentration, tubes are incomplete and not well interconnected (A).…”
Section: Discussionmentioning
confidence: 99%
“…10,12 The role of angiogenesis in vasculitis has begun to be investigated. We have shown that angiogenesis is observed in vascular inflammatory lesions of patients with GCA, [13][14][15] polyarteritis nodosa, 16,17 and cryoglobulinemic vasculitis, 18 and that sera from patients with different types of vasculitis, including Wegener's granulomatosis, Takayasu's disease, and GCA, have angiogenic activity. 19 We have proposed that angiogenesis may have a dual role in vasculitis.…”
mentioning
confidence: 92%
“…Interleukin-2 receptor-α (IL-2Rα, CD25) is upregulated on macrophages and lymphocytes by cytokines, such as interferon-γ, interleukin-2 and interleukin-3 [19, 20], or by nonspecific stimulation of human monocytes with lipopolysaccharides [21]. Using antibodies against IL-2Rα as an indicator of inflammatory activation [22], we tested the hypothesis that u-PA colocalized more with activated inflammatory cells compared to the whole population of macrophages in atherosclerotic vessels.…”
Section: Introductionmentioning
confidence: 99%